Yes‐associated protein promotes early hepatocyte cell cycle progression in regenerating liver after tissue loss. Issue 1 (27th November 2018) - Tschuor, Christoph; Kachaylo, Ekaterina; Ungethüm, Udo; Song, Zhoulun; Lehmann, Kuno; Sánchez‐Velázquez, Patricia; Linecker, Michael; Kambakamba, Patryk; Raptis, Dimitri A.; Limani, Përparim; Eshmuminov, Dilmurodjon; Graf, Rolf; et al.
Abstract: The ability of the liver to restore its original volume following tissue loss has been associated with the Hippo‐YAP1 pathway, a key controller of organ size. Yes‐associated protein 1 (YAP1)—a growth effector usually restrained by Hippo signaling—is believed to be of particular importance; however, its role in liver regeneration remains ill‐defined. To explore its function, we knocked down YAP1 prior to standard 70%‐hepatectomy (sHx) using a hepatocyte‐specific nanoformulation. Knockdown was effective during the major parenchymal growth phase (S‐phase/M‐phase peaks at 32 hours/48 hours post‐sHx). Liver weight gain was completely suppressed by the knockdown at 32 hours, but was reaccelerated toward 48 hours. Likewise, proliferative markers, Ccna2/b2 and YAP1 target gene expression were downregulated at 32 hours, but re‐elevated at 48 hours post‐sHx. Nonetheless, knockdown slightly compromised survival after sHx. When assessing a model of resection‐induced liver failure (extended 86%‐hepatectomy, eHx) featuring deficient S‐ and M‐phase progression, YAP1 was not induced at 32 hours, but upregulated at 48 hours post‐eHx, confirming its dissociation from M‐phase regulation. Therefore, YAP1 is vital to push hepatocytes into cycle and through the S‐phase, but is not required for further cell cycle progression during liver regeneration. The examination of YAP1 in human livers suggested its function is conserved in the regenerating mammalian liver.